Miles Morales. Vol. 8, Empire of the spider - Ahmed, Saladin (Marvel Worldwide, Inc., 2022)
"Miles Morales and Shift must embark on an interdimensional quest! But the people who set out on this journey through the multiverse...aren't going to be the same people who come back. Why is that? Ask Ultimatum! Miles and Shift's first stop is Brooklyn -- but not the one they know. They're entering the Empire of the Spider! Prepare to discover a horrific timeline where Miles' clone Selim is victorious, and rules with an iron fist! Now, the only thing standing in the way of this evil Spider-Man's oppressive regime is a rebellion led by some familiar faces: General Ganke Lee -- and a very grown-up and extremely badass Capitán Billie Morales!"--Amazon.